PRODUCTION AND ELECTRICAL CHARACTERIZATION OF ZINC OXIDE BASED COMPOSITE MATERIALS - BIRO, SAFIYA JAMEEL BIRO (Fırat Üniveristesi, 2016)
ZnO-CdO kompoziti hidrotermal yöntemle hazırlandı. Nanokompozitin yapısal, morfolojik, optik ve elektriksel özellikleri sırasıyla X-ışını kırınımı (XRD), FTIR, taramalı elektron mikroskobu (SEM), UV-VIS-NIR spektrofotometre ve iki prob kullanılarak gerçekleştirilmiştir. Termal kararlılığı belirlemek için TGA-DA analizi yapıldı. Bileşim analizi EDX ile yapıldı. Kompozitin bant aralığı, Zn prekürsörünün içeriğinin arttırılması ile birlikte sırasıyla 2.84, 2.78 and 3.06 eV olarak bulunmuştur. Anahtar Kelimeler: Çinko oksit, hidrotermal metod.

PRODUCTION AND ELECTRICAL CHARACTERIZATION OF ZINC OXIDE BASED COMPOSITE MATERIALS ZnO-CdO composite was prepared with hydrothermal method. The structural, morphological, optical, and electrical properties of the nanocomposite have been carried out using X-ray diffraction (XRD), FTIR, scanning electron microscopy (SEM), UV-VIS-NIR spectrophotometer, and two probe, respectively. TG-DTA analysis was done to determine the thermal stability. The compositional analysis was done by EDX. The band gap of the composite were found to be 2.84, 2.78 and 3.06 eV respectively with increasing the content of Zn precursor. Keywords: Zinc oxide, hydrothermal method.
ZnO esaslı kompozit malzemelerin üretilmesi ve elektriksel karakterizasyonu
Keywords: Fizik ve Fizik Mühendisliği